Multi-Channel ScanSAR for High-Resolution Ultra-Wide-Swath Imaging - Gebert, Nicolas; Krieger, Gerhard; Moreira, Alberto (European Conference on Synthetic Aperture Radar (EUSAR), 2008)
Multi-channel radar systems enable to overcome the inherent limitation of conventional synthetic aperture radar (SAR). An example is the combination of digital beamforming on receive in elevation with multi-aperture SAR signal reconstruction in azimuth which allows for high-resolution wide-swath imaging. In a next step, focus is turned to advanced concepts for the imaging of even wider swaths with high geometric resolution in azimuth. In this context, the operation of multi-channel SAR systems in burst modes like ScanSAR or TOPS-SAR is investigated and aspects of applying the multi-aperture reconstruction algorithm in combination with burst mode operation is analyzed. The impact of the digital processing network on the SNR and the azimuth ambiguities in multi-channel burst mode systems are considered and embedded in the design example of a ScanSAR system that enables the imaging of a 400 km wide swath with a geometric resolution of 5 m.
DLR Import::2019-04-03